Gambaran Hasil Pemeriksaan Histopatologi Penderita Tuberkulosis Jaringan Lunak di Laboratorium Patologi Anatomi Rumah Sakit Umum Madani Medan Periode 2020-2024 - Hutapea, Risma Ronauli; Lina, Juliana; Lister, Clarissa (Syntax Corporation, 2025)
Soft tissue tuberculosis is a rare form of extrapulmonary tuberculosis characterized by Mycobacterium tuberculosis infection of the subcutaneous tissue. This condition is important to recognize because its symptoms are nonspecific and often mimic malignancy, often referred to as a